Analisis PSAK 210 : Peristiwa Setelah Periode Pelaporan atas Dampak Isu Boikot Global terhadap PT Unilever Indonesia Tbk Tahun 2024 - Liza Riskiani Putri; Silva Anggraini; Nur Dimas; Fajar Subekti; Rimi Gusliana Mais (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to analyze the application of Statement of Financial Accounting Standards (PSAK) 210 Events After the Reporting Period to the case of a global boycott that impacted PT Unilever Indonesia Tbk in 2024, in response to the geopolitical conflict that occurred at the end of 2023. This phenomenon had a significant reputational and social impact, although it did not directly affect the financial position as of December 31, 2023. This study uses a descriptive-quantitative approach with a documentary analysis method of Unilever Indonesia's financial statements and sustainability reports for the 2023–2024 fiscal year. The analysis results show that the global boycott is categorized as a non-adjusting event, as it occurred after the reporting date and did not provide additional evidence regarding pre-existing conditions. However, this event is material in social and reputational terms, so it needs to be disclosed in the Notes to the Financial Statements (CALK) in accordance with the provisions of PSAK 210 and Auditing Standards (SA) 560. The 9% decline in net sales and 29.8% decline in net profit in 2024 indicate that reputational impact has an effect on the company's financial performance. This study emphasizes the importance of integrating financial reporting and sustainability (ESG disclosure) in strengthening corporate transparency and social accountability. These findings have implications for auditors, regulators, and management to broaden their understanding of the materiality of non-financial social events as part of subsequent events disclosure.